Rediscovery and Lectotypification of Eugenia argentea Bedd. (Myrtaceae) An Endemic and Endangered Species of India (Journal of Scientific Research, 2010)
Eugenia argentea Bedd. has been rediscovered from Wayanadu forests in Kerala after a lapse of 138 years of its first collection. Detailed description, photographs, lectotypification, etc are provided.Keywords:  Eugenia argentea; Rediscovery; Western Ghat; Lectotypification.© 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi:10.3329/jsr.v3i1.6210                J. Sci. Res. 3 (1), 213-216 (2011)